MENINGKATKAAN KEMAMPUAN BERBAHASA ANAK USIA DINI MELALUI MEDIA BUKU BERGAMBAR - Devi Tarigan; Juli Yanti Harahap (STKIP Subang, 2024)
Early childhood education is the beginning in forming a child's character and attitudes. Early childhood knowledge and learning strategies are required. This is necessary to explore children's interest in language skills. Early childhood language skills can arise when there is external stimulation. One way is through pictorial media. This research discusses the low language skills of young children. Based on children's problems, several children's problems can be identified, namely in expressing words, children have difficulty in stringing words together, many children are still shy about conveying words to the teacher during learning activities in class, children less independent in class activities, children do not know vocabulary and words, which means that children cannot differentiate between the words that children say and are still not perfect. The aim of this research is to improve the language skills of early childhood through picture books for children aged 5-6 years in Namarome Kindergarten child Mary. This type of research is classroom action research (PTK) using the picture book storytelling method for children aged 5-6 years at Mary's Children's Kindergarten Namorambe T.A 2022/2023. This research consisted of two cycles, namely cycle I and cycle II. At each meeting the researcher carried out learning outcomes tests on children to determine the child's improvement. In the pre-cycle the children's average score was 38%, in the first cycle the average score was 64.32%. in cycle II the average was 89% and the percentage of children categorized as developing very well each cycle also increased. Using the picture book storytelling method can improve the language skills of young children at Mary's Children's Kindergarten Namorambe T.A 2022/2023.